Open-source code for analysis of the lifetime total physical activity questionnaire (LTPAQ) - Coral Sánchez-Martín; Javier Leal-Martín; Timo Rantalainen; Irene Rodríguez-Gómez; Luis M. Alegre; Ignacio Ara (Heliyon)
Advancing research to understand the impact of lifetime physical activity patterns on health is essential. While some progress on the topic has been made, further research is nevertheless warranted. Openly accessible operational resources for processing and analysing longitudinal physical activity data would help advance the field. The Lifetime Total Physical Activity Questionnaire (LTPAQ) provides an in-depth and detailed record of occupational/volunteer, household and recreational physical activities conducted across the lifespan. Despite the authors describing a specific code for physical activity data processing, its lack of comprehensiveness hinders its implementation by researchers or health professionals with limited programming or software expertise. For this purpose, we aimed to develop an open-source MATLAB code to simplify data handling and enhance comparability between studies using the LTPAQ. The source code of the LTPAQ analysis is accessible on our Git repository (https://github.com/coralsanchezmartin/LTPAQ_MATLAB_code). This code automates data handling, ensuring efficiency and facilitating adaptability. Moreover, it interacts seamlessly with Microsoft Excel sheets, providing a user-friendly interface for data input, storage, and organisation. This approach, combined with ongoing efforts to refine the code, seeks to overcome LTPAQ's scoring complexities, and promote a standardised methodology. By facilitating the processing of physical activity data from this questionnaire, our tool is expected to encourage its application in epidemiological studies and foster new insights into the impact of lifestyle from a life course perspective, ultimately playing a crucial role in shaping public health policies and enhancing clinical practice.